PRAGMATIC MARKERS IN INTERCULTURAL ACADEMIC EMAIL COMMUNICATION - James Anderson (International Journal of Literature and Language Studies, 2026)
This article investigates the use of pragmatic markers in intercultural academic email communication within the broader field of linguistics and applied language studies. The study uses one hundred and twenty anonymised emails written by international postgraduate students to academic staff and applies pragmatic discourse analysis with attention to openings, requests, hedges, gratitude, and closings. The main finding is that writers used markers such as please, kindly, I was wondering, and thank you to manage social distance and institutional hierarchy. The article argues that explicit teaching of email pragmatics may reduce misunderstanding in international academic settings. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.